Сulturological analysis of petroglyphs “The glory of the ancient Turks”, “Flag bearer”, and “The war of horsemen and foot archers” related to the culture of the ancient Turks in Kazakhstan - Tatiyev, E.E.; Kenispaev, Zh.K.; Sarkulova, M.S.; Mukhamediyeva, A. B. (Karagandy University of the name of acad. E.A. Buketov, 2022)
Today, the creation of Cultural Studies in Kazakhstan is one of the most important tasks. One of the sources of culture in this field of science is spiritual and material values, the fundamental values of our knowledge. In this regard, the article considers petroglyphs of the ancient Turkic period – monuments of material values of history and culture. The ancient Turkic era is a powerful period of military hegemonic policy. Therefore, the article discusses and presents to the reader images of military scenes of that era in stone relief. The authors of the article, having conducted a scientific analysis of the material values of historical time, set the goal of how to implement it.
Keywords: ancient Turks; petroglyphs; historical and cultural heritage; material values; battle scenes; flags; ethnography; Cultural Studies analysis; cognitive knowledge; survey